Implementation of Problem Based Learning (PBL) to Increase Student Activeness in Reproductive System Subject at SMA Negeri 6 Madiun - Kartikasari, Rr. Intan; Banconowati, Mawar; Pujiati, Pujiati (Jurnal Pendidikan Biologi, 2023)
Education is a learning process connected with mutual interaction between students, teachers and learning resources. The activeness of students is very necessary to create an effective learning atmosphere. The research that has been conducted aims to increase activeness during the learning process by students with Biology subjects on reproductive system subject. The research was conducted by applying the Problem Based Learning (PBL) approach in class XI MIPA 1 SMA Negeri 6 Madiun. Data was collected through an observation sheet format containing a rubric for assessing student activeness. The analytical technique processed in this study uses descriptive analysis in the form of percentages. Based on the results of the study, there was an increase in the indicators of cooperation and social relations with a maximum score of 83.3% of students. The indicator give an opinion with a maximum score of 58.3% of students, teacher interaction with a maximum score of 50% and presenting the result of discussion with a maximum score of 36.1%. Based on research data, it shows that the application of Problem Based Learning (PBL) is effectively carried out in biology subjects. Learners tend to be more active and can collaborate well in group discussions. This research can help teachers provide solutions to overcome the probem of student inactivity in class. The application of learning model with Problem Based Learning (PBL) will be improved ctitical thinking of students.